PENGENDALIAN BANJIR SUNGAI BENGKANG UNTUK MENDUKUNG KAWASAN EKONOMI KHUSUS MANDALIKA - DEWANDHA MAS AGASTYA; I WAYAN YASA; HUMAIROH SAIDAH; MUH BAGUS BUDIANTO; I DEWA GEDE JAYANEGARA (Universitas Mahasaraswati K. Mataram, 2024)
Changes in land use that have occurred over a period of several years in the Kuta area have resulted in a lack of water catchment areas. The impacts caused by the lack of catchment areas are flooding and reduced water quality in rivers. The flood disaster in the Bengkang River caused damage to bridge infrastructure and people’s homes. The Bengkang river basin is divided into 3 sub – basins with a total area of 10,45 km2. Based on the results of the design flood analysis using the Nakayasu synthetic unit hydrograph method, the largest flood discharge value was obtained, namely 32,859 m3/second for a return period of 25 years. Hydraulic modeling was carried out to determine the water level and the ability of the river section to receive flow using HEC-RAS 6.1 software. Based on the simulation results with a return period of 5 years, it is known that flooding occurs in the middle and lower reaches of the Bengkang River, so structural mitigation is needed, namely normalization and repair of embankments. A 25-year return period flow simulation was carried out using a cross – section of the channel plan and no runoff was obtained in the Bengkang River.